In Situ (Operando) Electrochemical Dilatometry as a Method to Distinguish Charge Storage Mechanisms and Metal Plating Processes for Sodium and Lithium Ions in Hard Carbon Battery Electrodes. Issue 8 (20th July 2021) - Escher, Ines; A. Ferrero, Guillermo; Goktas, Mustafa; Adelhelm, Philipp
Abstract: In situ (operando) electrochemical dilatometry (ECD) provides information on the expansion/shrinkage of an electrode during cell cycling. It is shown that the ECD signal can be used as descriptor to characterize the charge storage behavior of lithium and sodium ions in hard carbon electrodes. It is found that sodium storage in hard carbons occurs by a three‐step mechanism, namely I) insertion, II) pore filling, and III) plating. Step III can be seen from a sudden increase in electrode thickness for potentials below around 36 mV versus Na + /Na and is assigned to plating on the hard carbon surface. Interestingly, this last step is absent in the case of lithium which demonstrates that the storage behavior between both alkali metals is different. The plating mechanism is also supported by reference experiments in which bulk plating is enforced. Bulk plating on hard carbon electrodes can be detected more easily for sodium compared to lithium. It is also found that the type of binder strongly influences the dilatometry results. A comparison between the binders sodium salt of carboxymethyl cellulose and poly(vinylidene difluoride) shows that the use of the former leads to notably smaller first electrode expansion as well as a higher initial Coulomb efficiency. Abstract : Plating only for sodium: The storage mechanism of sodium and lithium ions in hard carbon is investigated by monitoring the change of the electrode thickness during charging and discharging. For lithium ions, a two‐step mechanism is found, whereas for sodium ions, a three‐step mechanism with a plating process as the last mechanism is found.